Ellis—van Creveld Syndrome with Sagittal Craniosynostosis. Issue 2 (June 2015) - Fischer, Andrew S.; Weathers, William M.; Wolfswinkel, Erik M.; Bollo, Robert J.; Hollier, Larry H.; Buchanan, Edward P.
Ellis—van Creveld syndrome (EVC) is a rare disorder (the incidence is estimated at around 7/1, 000, 000) characterized by the clinical tetrad of chondrodystrophy, polydactyly, ectodermal dysplasia, and cardiac anomalies. Sagittal synostosis is characterized by a dolichocephalic head shape resulting from premature fusion of the sagittal suture. Both are rare disorders, which have never been reported together. We present a case of EVC and sagittal synostosis. We report the clinical features of a Hispanic boy with EVC and sagittal craniosynostosis who underwent cranial vault remodeling. The presentation of this patient is gone over in detail. A never before reported case of EVC and sagittal synostosis is presented in detail.